Protected Designation of Origin Extra Virgin Olive Oils Assessment by Nuclear Magnetic Resonance and Multivariate Statistical Analysis: "Terra di Bari", an Apulian (Southeast Italy) Case Study. (2nd January 2016) - Del Coco, Laura; Mondelli, Donato; Mezzapesa, Giuseppe Natale; Miano, Teodoro; De Pascali, Sandra Angelica; Girelli, Chiara Roberta; Fanizzi, Francesco Paolo
Abstract: We report a study on the chemical characterization of 102 monovarietal micro‐extracted and genetically characterized extra virgin olive oils (EVOOs) from Coratina, Ogliarola Barese and Cima di Mola cultivar, according to "Terra di Bari" (Apulia, southeast Italy) PDO requirement. Three additional geographical mentions, all belonging to the same Bari district (Bitonto, Castel del Monte and Murgia dei Trulli e delle Grotte), were studied and potential microclimate differences were evaluated. Our results indicate the possibility of distinguishing EVOOs from the same "Terra di Bari" PDO with respect to different cultivars and (to some extent) different subareas. In particular, two cultivars (Ogliarola Barese and Coratina), obtained from the same Bitonto area, and a single cultivar (Coratina), obtained from Bitonto and Castel del Monte subareas, were compared to investigate the micro‐area pedoclimatic effect. Finally, 1 H NMR data were found significant for classification purposes of unknown EVOO samples, the results of which were included in the model space, as they were correctly predicted by the OPLS‐DA obtained by 1 H NMR data. This work aims to classify commercial "Terra di Bari" PDO EVOOs by comparison of the declared cultivar and geographical origin with a reference dataset of genetically characterized micro‐extracted monovarietal oils. In conclusion, the effect of the pedoclimatic micro‐areas of origin on the Coratina cultivar, which is the main component of the "Terra di Bari" PDO, has been studied in order to improve the traceability of the raw material used to produce this valuable food.